Mineral Admixtures in Concrete: A Review on Performance Enhancement and Environmental Benefits - Shallaw Abdullah; Herish Faraj; Asmaa Abdulmajeed (Advances in Civil Engineering and Environmental Science, 2025)
This study provides an in-depth examination of the role and influence of mineral admixtures in enhancing the performance and sustainability of concrete, addressing both environmental and structural challenges faced by the global construction industry. Mineral admixtures, such as fly ash, silica fume, metakaolin, and slag, offer a sustainable alternative to traditional cement by significantly reducing CO2 emissions from cement production while improving the mechanical and durability properties of concrete. Extensive research and experimental findings demonstrate that these admixtures enhance compressive and tensile strength, improve workability, and provide better resistance to environmental factors. By strategically substituting natural aggregates with these materials, cement production can be reduced by over 50% without compromising essential mixed qualities. This study also highlights the synergistic effects of combining multiple admixtures to optimize mix designs, resulting in durable and high-performance concrete. Furthermore, the findings emphasize the potential of mineral admixtures to produce dense and sustainable concrete structures that meet the dual demands of environmental sustainability and structural efficiency. This research serves as a comprehensive resource for construction professionals and researchers, showcasing the critical importance of mineral admixtures in advancing sustainable practices and addressing modern construction challenges.